How Can We Use Computational Modeling to Improve Total Knee Arthroplasty? Modeling Stability and Mobility in the Implanted Knee. (February 2017) - Rullkoetter, Paul J.; Fitzpatrick, Clare K.; Clary, Chadd W.
Abstract : Validated computational models promise a virtual platform to create optimal articular surfaces that best achieve desired implant characteristics. Today, designers can parametrically define the primary geometric features of an implant, and automatically modify design variables until stability/mobility performance objectives are best achieved. This preclinical, virtual design iteration minimizes the development cycle compared with testing physical prototypes and, by evaluating a broader scope of design concepts, likely improves the clinical performance of the final product. However, the scenario described is not without shortcomings and requires thorough understanding of the capabilities and the limitations of the models used. Although models typically represent the articular interface well, the interaction with the patient and the surgical process includes significant variability and increase in complexity. We present current modeling capabilities for the estimation of implant stability/mobility, with further suggestions for answering the difficult question of how an implant might perform throughout the population.